RNAi-mediated gene silencing of Phlebotomus papatasi defensins favors Leishmania major infection - Vomáčková Kykalová, Barbora; Sassù, Fabiana; Volf, Petr; Telleria, Erich Loza (Frontiers in Physiology, 2023)
Production of different antimicrobial peptides (AMPs) is one of the insect's prominent defense strategies, regulated mainly by Toll and immune deficiency (IMD) humoral pathways. Here we focused mainly on two AMPs of Phlebotomus papatasi, vector of Leishmania major parasites, their association with the relish transcription factor and the effective participation on Leishmania infection. We further characterized the role of previously described gut-specific P. papatasi defensin (PpDef1) and identified the second defensin (PpDef2) expressed in various sand fly tissues. Using the RNAi-mediated gene silencing, we report that the silencing of PpDef1 gene or simultaneous silencing of both defensin genes (PpDef1 and PpDef2) resulted in increased parasite levels in the sand fly, detectable by qPCR, and higher sand fly mortality. In addition, we knocked down relish, the sole transcription factor of the IMD pathway, to evaluate the association of the IMD pathway with AMPs expression in P. papatasi. We demonstrated that the relish gene knockdown reduced the expression of PpDef2 and attacin, another AMP abundantly expressed in the sand fly body. Altogether, our experiments show the importance of defensins in the sand fly response toward L. major and the role of the IMD pathway in regulating AMPs in P. papatasi.